Effectiveness of Home-Based Occupational Therapy on COPM Performance and Satisfaction Scores in Patients with COPD. (March 2021) - Koolen, Eleonore H.; Spruit, Martijn A.; de Man, Marianne; Antons, Jeanine C.; Nijhuis, Elieke; Nakken, Nienke; Janssen, Daisy J.A.; van 't Hul, Alex J.
Background: Occupational therapy (OT) may be an important intervention in patients with COPD, but studies show conflicting results. Purpose: To evaluate the effectiveness of home-based monodisciplinary OT in COPD patients Method: We conducted an observational clinical study. Main outcomes were the mean differences in the Canadian Occupational Performance Measure (COPM) performance and satisfaction scores, pre and post intervention. Findings: Pre- and postintervention data were obtained from 41 patients. Statistically significant increases were observed in COPM performance (5.0 ± 1.1 versus 6.9 ± 0.9; P<0.001) and satisfaction (4.6 ± 1.3 versus 6.9 ± 1.0; P<0.001). The most frequently reported occupational performance problems were found in the domains of productivity (47%) and mobility (40%), fewer in self-care (10%) and the least in leisure (3%). Implications: Home-based monodisciplinary OT can contribute significantly to the improvement of daily functioning of patients with COPD. OT should therefore be considered more often as part of the integrated management of these patients.